COMMONWEALTH OF INDEPENDENT STATES: TRANS-ASIAN DEVELOPMENT CORRIDOR - KOMAROV, Vyacheslav (CENTRAL ASIA AND THE CAUCASUS, 2005)
The current importance of developing investment activity in the economic space of the CIS states is determined by the complicated problems that have arisen in mutual economic relations in connection with the breakup of the U.S.S.R. and the establishment of a Commonwealth of Independent States by 12 FSU republics. The disruption of their former technological-cooperation, infrastructural, trade, social and technological-information ties has led to the emergence of totally new political and economic realities in the post-Soviet space. The establishment of the CIS resulted from an awareness of the need to continue cooperation in order to preserve at the transition stage the economic, technological and infrastructural potentials of the newly independent states. The development of interstate (cross-border) investment activity could become a key aspect of their effective interaction designed to end the economic crisis and to stabilize and boost their national economies. The protracted investment crisis in the CIS is the main obstacle in the way of transition to a new stage, the stage of economic growth and fundamental structural changes in the Commonwealth countries. Investment activity in each CIS state crucially depends on the possibilities and behavior of domestic investors. At the same time, the potential annual demand for foreign direct investment in these countries is estimated at over $45 billion. The attempts to pull out of the deep and systemic economic crisis by means of a policy of financial stabilization alone as pursued in some CIS republics for a number of years did not lead to any positive results. The decline in production and investment activity continued. In the current situation, it is necessary to change the conceptual approach to the methods required to overcome this crisis. The main line of effective economic policy should be investment support for pilot sectors and projects of the real economy aimed at a general stabilization and revival of industry and agriculture. These problems are strategic and common to all the CIS countries, even though each of them has its own peculiarities requiring different tactical approaches and adjustment to concrete conditions.